The lost one : a life of Peter Lorre - Youngkin, Stephen D. (University Press of Kentucky, 2005)
Often typecast as a menacing figure, Peter Lorre achieved Hollywood fame first as a featured player and later as a character actor who trademarked his screen performances with a delicately strung balance between good and evil. His portrayal of the grisly child murderer in Fritz Lang's masterpiece M (1931) catapulted him to international fame. Today, the Hungarian-born actor is also recognized for his riveting performances in The Man Who Knew Too Much (1934), The Maltese Falcon (1941), and Casablanca (1942). The first full biography of this major actor draws upon more than three hundred interviews, including conversations with directors Fritz Lang, Alfred Hitchcock, Billy Wilder, John Huston, Frank Capra, and Rouben Mamoulian. Author Youngkin examines Lorre's pivotal relationship with German dramatist Brecht, his experience as an émigré from Hitler's Germany, his battle with drug addiction, and his struggle with the choice between celebrity and intellectual respectability.--From publisher description.